Siah2 regulates tight junction integrity and cell polarity through control of ASPP2 stability. - Kim, H; Claps, G; Möller, A; Bowtell, D; Lu, X; Ronai, Z (2014)
Changes in cell adhesion and polarity are closely associated with epithelial cell transformation and metastatic capacity. The tumor suppressor protein ASPP (Apoptosis-Stimulating Proteins of p53) 2 has been implicated in control of cell adhesion and polarity through its effect on the PAR complex. Here we demonstrate that under hypoxic conditions, the ubiquitin ligase Siah (seven in absentia homolog)2 controls ASPP2 availability, with concomitant effect on epithelial cell polarity. LC-MS/MS analysis identified ASPP2 and ASPP1 as Siah2-interacting proteins. Biochemical analysis confirmed this interaction and mapped degron motifs within ASPP2, which are required for Siah2-mediated ubiquitination and proteasomal-dependent degradation. Inhibition of Siah2 expression increases ASPP2 levels and enhances ASPP2-dependent maintenance of tight junction (TJ) integrity, and polarized architecture in three dimensional (3D) organotypic culture. Conversely, increase of Siah2 expression under hypoxia decreases ASPP2 levels and the formation of apical polarity in 3D culture. In all, our studies demonstrate the role of Siah2 in regulation of TJ integrity and cell polarity under hypoxia, through its regulation of ASPP2 stability.